PENGARUH HARGA DAN CITRA DESTINASI TERHADAP MINAT BERKUNJUNG KEMBALI MELALUI KEPUASAN (Studi pada Wisatawan Umbul Sidomukti Semarang) - Timurti, Citra Sekar; Nugraha, Hari Susanta (Jurnal Ilmu Administrasi Bisnis, 2020)
The tourism industry is currently was developing and growing rapidly which made people look for a recreation or vacation with their friends and family. One of the tourism that exists in Central Java was Umbul Sidomukti Semarang which offers beautiful and comfortable natural attractions to visit. Umbul Sidomukti was a Nature Tourism Area in Semarang to encourage tourist satisfaction and also the interest of visiting it back. The purpose of this study was to understand about the effect of the price and the destination image on the interest of visiting back the tourism based on tourist satisfaction. This study used explanatory research type. The sampling technique used purposive accidental. The object of this study was Umbul Sidomukti Semarang tourists. To analyze the data, the writer used SPSS 21.0 for Windows. As the results of discussion, it proved several things such as an effect of price on tourist satisfaction with t arithmetic (9,491) > t table (1,984), an effect of destination image on tourist satisfaction with t arithmetic (11,061) > t table (1,984), an effect of price on interest of visiting back with t arithmetic (3,891) > t table (1,984), an effect of destination image on the interest of visiting back with t arithmetic (7,534) > t table (1,984), and an effect of tourist satisfaction on the interest of visiting back with t arithmetic (6,190) > t table (1,984). Based on the sobel and mediation test, there are an effect of the price on the interest of visiting back satisfaction with t arithmetic (4.6527) > t table (1.984), and the destination image of the interest of visiting back satisfaction with t arithmetic (1.458) > t table (1,984). The suggestions of this study were Umbul Sidomukti Semarang to adjust the prices and improve the destination image and a sense of tourist satisfaction, so as to increase the interest of visit it back.